PROFIL KEMAMPUAN BERPIKIR KRITIS DAN EFIKASI DIRI SISWA KELAS X SMA PADA MATERI IKATAN KIMIA - Nur Hidayah, Firda; Herlinawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The aim of this research is to determine the profile of students' critical thinking skills and self-efficacy in chemical bonding material. In chemistry learning, critical thinking skills are essential for students to understand concepts in depth. Critical thinking helps students analyze information, evaluate answers, draw conclusions, and provide appropriate reasons for a chemical phenomenon. In chemical bonding material, this ability is needed when students compare ionic, covalent, and metallic bonds, explain the relationship between the structure and properties of compounds, and solve problems that require reasoning. In addition to critical thinking skills, self-efficacy is also an important factor in the student learning process. Self-efficacy is a student's belief in their ability to complete tasks and face learning difficulties. This study is a descriptive study, involving one research subject. The population of this study was grade X students of Pencawan Medan Private High School. The sample used was the entire grade X students of Pencawan Medan Private High School, which consisted of three classes. Data collection used a critical thinking essay test and a Likert scale questionnaire. Data analysis in this study used descriptive analysis to determine the score and category of student profiles. The results showed that the average value of students' critical thinking was 67.87, which was included in the moderate category. The average score for student self-efficacy was 71.6, which is in the low category. It can be concluded that the profile of critical thinking skills and self-efficacy of grade 10 students at Pencawan Private High School is in the moderate category. Keywords: Critical Thinking Skills, Self-Efficacy, Chemical Bonding